Private health insurance : history, politics and performance - Thomson, Sarah (Professor in health policy); Sagan, Anna; Mossialos, Elias (Cambridge University Press, 2020)
Can private health insurance fill gaps in publicly financed coverage? Does it enhance access to health care or improve efficiency in health service delivery? Will it provide fiscal relief for governments struggling to raise public revenue for health? This book examines the successes, failures and challenges of private health insurance globally through country case studies written by leading national experts. Each case study considers the role of history and politics in shaping private health insurance and determining its impact on health system performance. Despite great diversity in the size and functioning of markets for private health insurance, the book identifies clear patterns across countries, drawing out valuable lessons for policymakers while showing how history and politics have proved a persistent barrier to effective public policy. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 13 Oct 2020).
Keywords: Health insurance -- Europe; Health insurance -- Government policy -- Europe; Health insurance premiums -- Europe; Medical care -- Europe